PELAKSANAAN PENGAWASAN KENDARAAN LAIK JALAN (STUDI KASUS BUS KOTA DI KOTA PEKANBARU) - Siallagan, Melgibson; Sadad, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Increased population growth and high mobility that occurred in Pekanbarucity requires adequate tools transfortation. City Bus is one of the modestransfortation in Pekanbaru city. Situation on the ground, conditions City Busoperating in Pekanbaru city on the wane and have poor condition, all on aging. Inaddition to the physical condition of complete comfort and safety of the vehicleare also many that do not exist. To complete transfortation tool that is safe,convenient and adequate, then the Department of Transportation Communicationand Information Pekanbaru City to controling the examination roadworthyvehicles operating in Pekanbaru city.Theory concept used is the theory of control, the indicators in this study asthe standard setting process, the process of assessment and corrective actionprocesses. While the informant of research in ground is the head of UPTD VehicleTesting, UPTD staff, employees and the owner or driver of a City Bus. This studyis a qualitative descriptive study.From the research can be concluded that the surveillance conducted UPTDVehicle Testing Pekanbaru City is still less than the maximum, this is becausethere are many vehicles or buses operating in Pekanbaru city that has passedtesting but his condition is still worrying or not roadworthy.Keywords: Management, Controlling, Transfortation